The Influence of Using Bingo Game Towards Students’ Vocabulary Mastery at the First Semester of the Seventh Grade of MTs N 2 Bandar Lampung in the Academic Year of 2016/2017 - Puspita, Nurul; Losari, Amelya Herda (Universitas Islam Negeri Raden Intan Lampung, 2016)
Vocabulary is one of the important language elements that should be mastered by the students. Based on the preliminary research at MTs N 2 Bandar Lampung, the researcher found that there were 67.70% students’ vocabulary score less than the standard minimun score (KKM) which is 75. The objective of this research was to know whether there is an influence of using bingo game towards students’ vocabulary mastery or not. The method of the research was quasi experimental design with the treatment held in three meetings, 2x40 minutes in each meeting. The population of this research was the seventh grade students of MTs N 2 Bandar Lampung. For taking the sample, the researcher used cluster random sampling. The sample was two classes, class VII H as the experimental class and class VII I as the control class. Both of them consisted of 32 students. In collecting the data, the researcher used tests. The researcher used the test instrument in the form of multiple choice. The test consisted of 40 items before validity test. After the validity test, the instrument test for pretest consisted of 22 items and posttest consisted of 22 items. For analyzing the data, the researcher used Mann Whitney Test. From the data analysis, it was found that the result of Mann Whitney Test was 0.000. This result is consulted to the score of the value significant generated Sig. (pvalue) < α = 0.05. Therefore, Ho is rejected and Ha is accepted. In other words, from this research it is known that bingo game can influence the students’ vocabulary mastery. It can be concluded that there is a significant influence of using bingo game towards students’ vocabulary mastery.